Morse v. Frederick’s New Perspective on Schools’ Basic Educational Missions and the Implications for Gay-Straight Alliance First Amendment Jurisprudence - Woods, Jordan Blair (Columbia Journal of Gender and Law, 2008)
Consider two eleventh grade students, Michael and Anna, who attend public high school in a suburban town. The high school has approximately 1,000 students and enforces an abstinence policy banning any discussion of sexual activity. Two years ago, Michael and Anna were the high school’s first students to openly identify as gay and lesbian. Now over twenty students openly identify as gay, lesbian, bisexual, transgender, or queer (LGBTQ). Recently, Michael and Anna discussed the growing interest among LGBTQ students and allies to form a gay-straight alliance (GSA) with one of their teachers. The teacher agreed to advise the GSA and filed a petition to the Board of Education to create the student group. The GSA’s mission was to provide students with a safe space at school to discuss anti-LGBTQ harassment and work together to promote tolerance and acceptance regardless of sexual orientation and gender identity. The Board of Education denied the GSA’s petition, claiming that allowing a “sex-based” group to meet on school grounds would violate the school’s abstinence policy and thus interfere with the school’s educational mission. This hypothetical is not uncommon. LGBTQ youth are becoming more open about their sexual orientations and gender identities, which has resulted in more efforts by students to form student groups to discuss issues surrounding sexual orientation and gender identity, and in turn greater resistance to the formation of GSAs from school districts that oppose them.’ LGBTQ students usually contend that GSA prohibitions violate their rights under the Federal Equal Access Act (EAA) and the First Amendment. Despite being presented with both EAA and First Amendment claims, most courts have avoided the First Amendment issue and resolved the cases solely on equal access grounds. This avoidance has created uncertainty with regard to the level of protection that the First Amendment affords students to form GSAs in public schools. As this uncertainty lingers, school districts become increasingly clever in creating their student organizations’ policies in ways that avoid triggering the EAA. Since the only alternative federal means of relief is under the First Amendment, the need for a clarification of the protection that the First Amendment affords students to form GSAs is particularly urgent.